Joermungandr bolti, an exceptionally preserved 'microsaur' from the Mazon Creek Lagerstätte reveals patterns of integumentary evolution in Recumbirostra. Issue 7 (21st July 2021) - Mann, Arjan; Calthorpe, Ami S.; Maddin, Hillary C.
Abstract : The Carboniferous Pennsylvanian-aged (309–307 Ma) Mazon Creek Lagerstätte produces some of the earliest fossils of major Palaeozoic tetrapod lineages. Recently, several new tetrapod specimens collected from Mazon Creek have come to light, including the earliest fossorially adapted recumbirostrans. Here, we describe a new long-bodied recumbirostran, Joermungandr bolti gen. et sp. nov., known from a single part and counterpart concretion bearing a virtually complete skeleton. Uniquely, Joermungandr preserves a full suite of dorsal, flank and ventral dermal scales, together with a series of thinned and reduced gastralia. Investigation of these scales using scanning electron microscopy reveals ultrastructural ridge and pit morphologies, revealing complexities comparable to the scale ultrastructure of extant snakes and fossorial reptiles, which have scales modified for body-based propulsion and shedding substrate. Our new taxon also represents an important early record of an elongate recumbirostran bauplan, wherein several features linked to fossoriality, including a characteristic recumbent snout, are present. We used parsimony phylogenetic methods to conduct phylogenetic analysis using the most recent recumbirostran-focused matrix. The analysis recovers Joermungandr within Recumbirostra with likely affinities to the sister clades Molgophidae and Brachystelechidae. Finally, we review integumentary patterns in Recumbirostra, noting reductions and losses of gastralia and osteoderms associated with body elongation and, thus, probably also associated with increased fossoriality.